Novel treatments to tackle myelofibrosis. Issue 11 (2nd November 2018) - Zimran, Eran; Keyzner, Alla; Iancu-Rubin, Camelia; Hoffman, Ronald; Kremyanskaya, Marina
ABSTRACT: Introduction : Despite the dramatic progress made in the treatment of patients with myelofibrosis since the introduction of the JAK1/2 inhibitor ruxolitinib, a therapeutic option that can modify the natural history of the disease and prevent evolution to blast-phase is still lacking. Recent investigational treatments including immunomodulatory drugs and histone deacetylase inhibitors benefit some patients but these effects have proven modest at best. Several novel agents do show promising activity in preclinical studies and early-phase clinical trials. We will illustrate a snapshot view of where the management of myelofibrosis is evolving, in an era of personalized medicine and advanced molecular diagnostics. Areas covered : A literature search using MEDLINE and recent meeting abstracts was performed using the keywords below. It focused on therapies in active phases of development based on their scientific and preclinical rationale with the intent to highlight agents that have novel biological effects. Expert commentary : The most mature advances in treatment of myelofibrosis are the development of second-generation JAK1/2 inhibitors and improvements in expanding access to donors for transplantation. In addition, there are efforts to identify drugs that target pathways other than JAK/STAT signaling that might improve the survival of myelofibrosis patients, and limit the need for stem-cell transplantation.